Assessing the influence of urbanization and energy on carbon emissions of Turkey: evidence using the new RALS analysis - Emir, Firat; Philip, Lucy Davou; Sertoglu, Kamil (Springer Heidelberg, 2022)
This research aimed at examining the nexus among urbanization, energy use, foreign direct investment (FDI), economic growth, and environmental sustainability in Turkey. Time-series data from 1970 to 2017 were used in the analysis, and ecological footprint was used as an indicator for environmental sustainability. The aim was to investigate the long-run nexus among the indicators and contribute to the literature in several ways. One of these contributions is to empirically investigate this relationship with the residual augmented least squares (RALS) augmented Dickey-Fuller ADF for stationarity test and RALS-EG (residual augmented least squares-Engle and Granger) for the long-run steady-state relationship of investigated variables. Together with, fully modified OLS (ordinary least squares) model has been employed to observe the long-run effect and the significance of the investigated variables on environmental sustainability. The results revealed that the long-run relationship exists and the long-run coefficients show statistically significant effects on environmental sustainability. In the long run, urbanization and energy usage degrade the environment and reduce environmental quality, although FDI inflow and gross domestic product (GDP) growth contribute 0.22% and 8.03% to environmental sustainability in Turkey, respectively. The environmental Kuznets curve (EKC) hypothesis is not valid in this model and U-shaped relationship was found between increasing economic performance and the ecological footprint. The causality results reflect that urbanization has feedback causality with energy use. The study suggests that to achieve sustainable urbanization, policymakers in Turkey should execute well-planned urbanization programs, create an energy conservation policy, and encourage green industries to ensure a sustainable increase in environmental quality for Turkey.
Keywords: Urbanization; Energy consumption; Ecological footprint; Turkey; RALS analysis; Environmental sustainability